Simulation model of security control lane operation in the state of the COVID-19 epidemic. (September 2020) - Kierzkowski, Artur; Kisiel, Tomasz
Abstract: The article presents a discrete event simulation model for the various security control lanes configurations. The aim of the article was to check the impact of social distance on the performance of security control lanes. Different ways of passenger flow across the lane were compared. The model was verified on actual data. The results obtained indicate that it is better to use lanes with a dedicated service area for each passenger on Entry Area than a free flow along the lane. This knowledge is extremely important for security checkpoint designers. It will help ensure proper performance under normal conditions and limit performance losses under epidemic conditions. The results were also divided according to different structure of the passenger stream (percentage share of flags, lowcost and charter operations). The results showed that this has a significant impact on efficiency. Highlights: 3 different configurations of the security control lane have been analysed. A simulation model was developed for 3 different passenger flow strategies. The division between lowcost, charter and flag passengers has been applied. The performance losses of lanes during the Covid-19 epidemic were checked. Reconfiguration of the system has been suggested as a corrective action.